The Survival of the Sunset Textile Industry Involving Bilateral Free-Trade Agreements: Empirical Evidences of Taiwan - Liu, Hsiang-Hsi; Wang, Teng-Kun (Asian Journal of Economic Modelling, 2018)
This study attempts to investigate how bilateral free-trade agreements (FTA) affect competitiveness within Taiwanese textile industry with comparison to other Asian Tiger countries (Hong Kong and South Korea) by utilizing export market share (EMS) and revealed comparative advantage (RCA). The applied regression model is estimated in order to identify which factors would affect the international competitiveness. The results have demonstrated that the gradually released quota by multi-fiber agreement (MFA) has a negative effect on the promotion of international competitiveness. On the other hand, it is estimated that the signing of bilateral FTAs such as economic cooperation framework agreement (ECFA) might substantially help Taiwanese textile industry’s international competitiveness. In hope to better understand the relationships between interconnected regional and global integration processes emerging from today’s challenging multilateral trading structure within Asia-Pacific regions.